Hsp70 facilitates trans-membrane transport of bacterial ADP-ribosylating toxins into the cytosol of mammalian cells - Katharina Ernst (Nature Portfolio, 2017)
Abstract Binary enterotoxins Clostridium (C.) botulinum C2 toxin, C. perfringens iota toxin and C. difficile toxin CDT are composed of a transport (B) and a separate non-linked enzyme (A) component. Their B-components mediate endocytic uptake into mammalian cells and subsequently transport of the A-components from acidic endosomes into the cytosol, where the latter ADP-ribosylate G-actin resulting in cell rounding and cell death causing clinical symptoms. Protein folding enzymes, including Hsp90 and peptidyl-prolyl cis/trans isomerases facilitate transport of the A-components across endosomal membranes. Here, we identified Hsp70 as a novel host cell factor specifically interacting with A-components of C2, iota and CDT toxins to facilitate their transport into the cell cytosol. Pharmacological Hsp70-inhibition specifically prevented pH-dependent trans-membrane transport of A-components into the cytosol thereby protecting living cells and stem cell-derived human miniguts from intoxication. Thus, Hsp70-inhibition might lead to development of novel therapeutic strategies to treat diseases associated with bacterial ADP-ribosylating toxins.